2018
DOI: 10.5194/piahs-379-105-2018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vegetation condition and its relationship with meteorological variables in the Yarlung Zangbo River Basin of China

Abstract: Abstract. The Yarlung Zangbo River Basin is located in the southwest border of China, which is of great significance to the socioeconomic development and ecological environment of Southwest China. Normalized Difference Vegetation Index (NDVI) is an important index for investigating the change of vegetation cover, which is widely used as the representation value of vegetation cover. In this study, the NDVI is adopted to explore the vegetation condition in the Yarlung Zangbo River Basin during the recent 17 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Ding et al (2018) demonstrated that alpine grasslands in Tibetan Plateau would face increasingly severe meteorological drought pressure in the future due to the negative influence of VPD. What's more, there is a significant correlation between vegetation degradation and climate change in the YZR basin, emphasizing the importance of VPD as the driving factor of drought (Han et al, 2018). Meanwhile, low correlations between scPDSI and air temperature were found in the YZR basin, indicating that meteorological drought variations were largely unaffected by temperature (Li et al, 2019a).…”
Section: Discussionmentioning
confidence: 96%
“…Ding et al (2018) demonstrated that alpine grasslands in Tibetan Plateau would face increasingly severe meteorological drought pressure in the future due to the negative influence of VPD. What's more, there is a significant correlation between vegetation degradation and climate change in the YZR basin, emphasizing the importance of VPD as the driving factor of drought (Han et al, 2018). Meanwhile, low correlations between scPDSI and air temperature were found in the YZR basin, indicating that meteorological drought variations were largely unaffected by temperature (Li et al, 2019a).…”
Section: Discussionmentioning
confidence: 96%
“…Considerable investigations have confirmed that elevation-dependent warming results in vegetation, glaciers, and snow cover, presenting distinctive properties at different altitudes [75,76], which in turn leads to a significant impact on the spatial distribution of TWSC. For example, in the YZRB, when the altitude is higher than 3250 m, the NDVI begins to decline gradually, and the NDVI gradually becomes stable as the elevation approaches 6000 m [77]. In addition, the elevation dependence of the warming rate has a significant implication for QTP water resources and environmental changes, since most glaciers and snow surfaces are located 5000 m above sea level [78].…”
Section: Time-lag Effect Of Monthly Twsc Estimationsmentioning
confidence: 99%
“…Therefore, investigation on how vegetation and climate have changed, and analysis of the effects of climate change on vegetation, could prove useful to support studies on runoff in the YZR basin. Previous studies have typically used conventional indicators (i.e., temperature and precipitation) to investigate the effects of variations of hydrological cycle components on vegetation in the YZR basin (Li et al 2015(Li et al , 2019Han et al 2018;Liu et al 2019;Sun et al 2019). Li et al (2019) detected a significant (nonsignificant) positive (negative) correlation between growing season NDVI and surface air temperature (precipitation) in the YZR basin.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%